2015
DOI: 10.1158/1078-0432.ccr-14-1194
|View full text |Cite
|
Sign up to set email alerts
|

Integrinβ6-Targeted Immunoliposomes Mediate Tumor-Specific Drug Delivery and Enhance Therapeutic Efficacy in Colon Carcinoma

Abstract: Purpose: Adjuvant chemotherapy is one of the significant treatments for colon cancer in clinic. However, it does not achieve the desired therapeutic efficacy, largely due to chemotherapeutic resistance. Integrinb6 (ITGB6) is expressed in malignant colonic epithelia, but not in normal epithelia, and is associated with the progression, metastasis, and chemotherapeutic resistance of colon cancer. Accordingly, it is necessary to design therapeutic approaches for efficient and targeted drug delivery into ITGB6-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 42 publications
2
41
0
1
Order By: Relevance
“…According to recent studies, Itgb6 is related to multiple carcinogenesis-related pathways, including migration, invasion, and survival (Moore et al, 2014). Liang et al (2015) reported that Itgb6-targeted immunoliposomes could provide a highly efficient method for targeted-drug transportation in colon cancer and therefore may represent a promising clinical anticancer therapy. To the best of our knowledge, this is the first report of Itgb6 hypomethylation in prenatal PTSD intervention.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, Itgb6 is related to multiple carcinogenesis-related pathways, including migration, invasion, and survival (Moore et al, 2014). Liang et al (2015) reported that Itgb6-targeted immunoliposomes could provide a highly efficient method for targeted-drug transportation in colon cancer and therefore may represent a promising clinical anticancer therapy. To the best of our knowledge, this is the first report of Itgb6 hypomethylation in prenatal PTSD intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin beta 6 mRNA expression, which is 7.7-fold higher in this subpopulation, has been shown as an independent predictor of survival, and high expression is associated with distant metastasis and poor survival in breast cancer (58) as well as in colon cancer where it also appears to confer chemoresistance (59). A number of upregulated secreted factors with roles in cancer metastasis, angiogenesis, and hypoxia (e.g., TGFB1, LOXL4, WNT4) add to the interpretation that these cells communicate actively with their surrounding and may have a more significant role in the interaction with the TME than their CD184 hi counterparts.…”
Section: Discussionmentioning
confidence: 96%
“…This result was dependent on the level of β6 expression found on the cell surface [74]. These immunoliposomes reduced the 5-FU IC50 for SW480 β6OE and HT-29 cells by >90 % and induced a ∼1.5-fold increase in the rate of 5-FU-induced apoptosis when compared to control liposomes [74]. Liang et al observed that the growthinhibiting activity of both the immunoliposomes and control liposomes was indistinguishable in non-β6-expressing SW480 Mock cells, indicating that the anti-tumour activity may be attributed to specific binding to β6 on the cell surface [74].…”
Section: αVβintegrin Is Intercellularly Transported Via Exosomes and mentioning
confidence: 94%
“…Liang et al were able to enhance cellular internalisation of β6-targeted immunoliposomes into β6-expressing SW480 β6OE and HT-29 cell lines compared to control liposomes. This result was dependent on the level of β6 expression found on the cell surface [74]. These immunoliposomes reduced the 5-FU IC50 for SW480 β6OE and HT-29 cells by >90 % and induced a ∼1.5-fold increase in the rate of 5-FU-induced apoptosis when compared to control liposomes [74].…”
Section: αVβintegrin Is Intercellularly Transported Via Exosomes and mentioning
confidence: 97%
See 1 more Smart Citation